A Technical Approach to Anesthesia in the Case of Tonsillectomy - Cahyo, Febrian Dwi; Sutanto, Bambang; Mahmuda, Iin Novita Nurhidayati (Fakultas Kedokteran Universitas Sebelas Maret Surakarta, 2023)
Background: Tonsillectomy is the most common surgical procedure performed by an ENT doctor (Throat Nose Ear) in children. This surgery can cause pain, bleeding and swelling in the injured throat. Patient may complain of pain, difficulty swallowing, eating, drinking disorders, nausea and vomiting and fall into a dehydrated state. This can reduce patient satisfaction.Discussion: Postoperative pain management of tonsillectomy is a concern both by the ENT doctor and by the anesthesiologist. The high incidence of post-tonsillectomy pain or anxiety increases the risk of secondary post-tonsillectomy bleeding. It is necessary to know the mechanism of post operative pain and the negative impact of pain.Conclusion: Doctors should give attention to reduce postoperative pain and choose a rational analgesic to overcome post operative tonsillectomy pain.